INFLUENCE DAMAGING OF THE PERINATAL FACTORS ON STATE NEONATAL BY SYMPTOMS OF GROWTH RETARDATION FETUS - Kuzmina, I.Yu. (The Journal of V. N. Karazin Kharkiv National University, series "Medicine")
The researches on revealing damaging of the perinatal factors on state by fetus were carried out. It was shown that perinatal outcomes at symptoms of growth retardation fetus (SGRF) were largely determined by fetal hypoxia, expressiveness of a growth retardation of fetus and method of delivery.